Patient-directed therapy during in-patient stroke rehabilitation: stroke survivors' views of feasibility and acceptability. (4th December 2015) - Horne, Maria; Thomas, Nessa; McCabe, Candy; Selles, Rudd; Vail, Andy; Tyrrell, Pippa; Tyson, Sarah
Abstract: Purpose : Patient-led therapy, in which patients work outside therapy sessions without direct supervision, is a possible way to increase the amount of therapy stroke patients' receive without increasing staff demands. Here, we report patients' views of patient-led mirror therapy and lower limb exercises. Method : 94 stroke survivors with upper and lower limb limitations at least 1-week post-stroke undertook 4 weeks of daily patient-led mirror therapy or lower limb exercise, then completed questionnaires regarding their experience and satisfaction. A convenience random sample of 20 participants also completed a semi-structured telephone interview to consider their experience in more detail and to capture their longer term impressions. Results : Participants were generally positive about patient-led therapy. About 71% found it useful; 68% enjoyed it; 59% felt it "worked" and 88% would recommend it to other patients. Exercise was viewed more positively than the mirror therapy. Difficulties included arranging the equipment and their position, particularly for more severe strokes, loss of motivation and concerns about working unsupervised. Conclusions : Patient-led mirror therapy and lower limb exercises during in-patient rehabilitation is generally feasible and acceptable to patients but "light touch" supervision to deal with any problems, and strategies to maintain focus and motivation are needed. Implications for Rehabilitation: Most stroke patients receive insufficient therapy to maximize recovery during rehabilitation. As increases in staffing are unlikely there is an imperative to find ways for patients to increase the amount of exercise and practice of functional tasks they undertake without increasing demands on staff. Patient-led therapy (also known as patient-directed therapy or independent practice), in which patients undertake exercises or functional tasks practice prescribed by a professional outside formal therapy sessions is one way of achieving this. It is widely used in community-based rehabilitation but is uncommon in hospital-based stroke care. We explored the feasibility and acceptability of two types of patient-led therapy during hospital-based stroke care; mirror therapy for the upper limb and exercises (without a mirror) for the lower limb. Here, we report patients' experiences of undertaking patient-led therapy. Patient-led mirror therapy and lower limb exercises during in-patient stroke rehabilitation is generally feasible and acceptable to patients but "light touch" supervision to deal with any problems, and strategies to maintain focus and motivation are needed.